Temirxanova Qumargul Aydosbay qizi - Temirxanova Qumargul Aydosbay qizi (International Journal of Literature and Language Studies, 2026)
This study presents a systematic and exhaustive evaluation of the paradigm shift governing 21st-century English Language Teaching (ELT), investigating the design, operational dynamics, and practical constraints of dominant instructional frameworks. Specifically, it contextualizes Task-Based Language Teaching (TBLT), Project-Based Learning (PBL), the Flipped Classroom model, and Technology-Enhanced Language Learning (TELL) within contemporary higher education environments. By executing a rigorous qualitative meta-synthesis of empirical data spanning from 2015 to 2024, this paper establishes how structural transitions from traditional teacher-led instruction to learner-centered, digitally mediated ecologies optimize language acquisition. The synthesis incorporates foundational socio-cultural theories alongside cognitive load parameters to examine how these methodologies function. It evaluates structural realities including large class sizes, cultural resistance to student autonomy, and systemic resource discrepancies often observed in regional and post-Soviet educational sectors. The findings underscore that while integrated models markedly enhance student agency and communicative competence, their institutional scalability relies on aligning professional development, adaptive curricula, and formative assessment designs. Ultimately, a balanced pedagogical framework is proposed to bridge theoretical ideals with pragmatic constraints.